The Effect of Digital Pocketbook on Anemia-Related Health Literacy and Anemia Prevention Awareness among Elementary School Students - Prima Trisna Aji; Tukimin Bin Sansuwito; Elinda Rizkasari (Pedagogik Journal of Islamic Elementary School, 2026)
Anemia remains a significant health concern among school-aged children because it can adversely affect cognitive development, concentration, academic performance, and overall well-being. Despite the importance of early prevention, many elementary school students have limited understanding of anemia-related health information, which may hinder the development of preventive health awareness. This study aimed to examine the effect of a Digital Pocketbook on health literacy and anemia prevention awareness among elementary school students. A quantitative study employing a quasi-experimental pretest–posttest control group design was conducted among 60 fifth-grade students selected through purposive sampling and assigned to an intervention group (n = 30) and a control group (n = 30). The intervention consisted of a multimedia-based Digital Pocketbook containing visual illustrations, concise learning modules, and interactive reflective activities related to anemia prevention, which was implemented for four weeks. Data were collected using the Health Literacy Questionnaire for Elementary Students (HLQ-ES) and the Anemia Prevention Awareness Questionnaire (APAQ). The results revealed that students in the intervention group experienced significantly greater improvements in health literacy and anemia prevention awareness than those in the control group (p < 0.001). Large effect sizes were observed for health literacy (d = 1.85) and anemia prevention awareness (d = 1.92), indicating substantial educational benefits of the intervention. These findings suggest that the Digital Pocketbook is an effective educational medium for strengthening students’ understanding of anemia-related health information and enhancing preventive health awareness. Future studies should investigate whether these improvements translate into sustained preventive health behaviors.